Industrial Training Report: Perpustakaan Politeknik Kuching / Norzieana Mohammad Nasir - Mohammad Nasir, Norzieana (Faculty of Information Management, 2019)
Industrial training is one of the compulsory study requirements in order to fulfill students to hold a degree. It is a challenge to anyone who involved on it. I have chosen to do my internship at two different libraries which are academic library, Perpustakaan Politeknik Kuching Sarawak, and public library, Pustaka Negeri Sarawak. I have been in both organizations for 5 months starting 1st August 2019 until 31st October 2019 at Perpustakaan Politeknik Kuching Sarawak, meanwhile from 1st November 2019 until 31st December 2019 at Pustaka Negeri Sarawak. The report of this industrial training consists of 4 chapters which are the introduction, organizational information, industrial training activities, and industrial training reflection. The main inputs for this report are in chapter 3 and chapter 4. I will explain in details about the activities and tasks have been done within 5 months of my industrial training as well as the special project I have done for Perpustakaan Politeknik Kuching Sarawak. Chapter 4 will cover about my knowledge gained, personal thoughts, lesson learnt, and limitation and suggestion from my perspective. I have been exposed to the working environment and obtain many knowledge and experiences during my industrial training.